Efficient Sorption of Arsenic on Nanostructured Fe-Cu Binary Oxides: Influence of Structure and Crystallinity - Zhang, Gaosheng; Wu, Zhijing; Qiu, Qianying; Wang, Yuqi (Frontiers in Chemistry, 2022)
To study the structure-performance relationship, a series of nanostructured Fe-Cu binary oxides (FCBOs) were prepared by varying synthesis conditions. The obtained binary oxides were well characterized using X-ray diffraction (XRD), transmission electron microscope (TEM), Brunner-Emmet-Teller (BET), magnetic and Zeta potential measurement techniques. Both As(V) and As(III) sorption on the FCBOs were evaluated by batch tests. Results show that the surface structure and crystallinity of FCBOs are greatly dependent on preparation conditions. The crystallinity of FCBOs gradually increases as the synthesis pH value increasing from 9.0 to 13.0, from amorphous phase to well-crystalline one. Simultaneously, the morphology change of FCBOs from irregular agglomerate to relatively uniform polyhedron has been observed. The sorption of arsenic is greatly influenced by the crystallinity and structure of FCBOs, decreasing with increasing degree of crystallinity. The amorphous FCBO has higher surface hydroxyl density than well-crystalline one, which might be the reason of higher sorption performance. As(V) is sorbed by the FCBOs via formation of inner-sphere surface complexes and As(III) is sorbed through formation of both inner- and outer-sphere surface complexes. This investigation provides new insights into structure-performance relationship of the FCBO system, which are beneficial to develop new and efficient sorbents.